Novel rat tail discitis model using bioluminescent Staphylococcus aureus. Issue 9 (15th March 2017) - Bostian, Phillip A.; Karnes, Jonathan M.; Cui, Shari; Robinson, Lisa J.; Daffner, Scott D.; Witt, Michelle R.; Emery, Sanford E.
ABSTRACT: Management of spondylodiscitis is a challenging clinical problem requiring medical and surgical treatment strategies. The purpose of this study was to establish a rat model of spondylodiscitis that utilizes bioluminescent Staphylococcus aureus ( S. aureus ), thus permitting in vivo surveillance of infection intensity. Inocula of the bioluminescent S. aureus strain XEN36 were created in concentrations of 10 2 CFU/0.1 ml, 10 4 CFU/0.1 ml, and 10 6 CFU/0.1 ml. Three groups of rats were injected with the bacteria in the most proximal intervertebral tail segment. The third most proximal tail segment was injected with saline as a control. Bioluminescence was measured at baseline, 3 days, and weekly for a total of 6 weeks. Detected bioluminescence for each group peaked at day 3 and returned to baseline in 21 days. The average intensity was highest for the experimental group injected with the most concentrated bacterial solution (10 6 CFU/0.1 ml). Radiographic analysis revealed loss of intervertebral disc space and evidence of osseous bridging. Saline‐injected spaces exhibited no decrease in intervertebral spacing as compared to distal sites. Histologic analysis revealed neutrophilic infiltrates, destruction of the annulus fibrosus and nucleus pulposus, destruction of vertebral endplates, and osseous bridging. Saline‐injected discs exhibited preserved annulus fibrosus and nucleus pulposus on histology. This study demonstrates that injection of bioluminescent S. aureus into the intervertebral disc of a rat tail is a viable animal model for spondylodiscitis research. This model allows for real‐time, in vivo quantification of infection intensity, which may decrease the number of animals required for infection studies of the intervertebral disc. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2075–2081, 2017.